Where did Christopher Columbus start?: The estuarine scenario of a historical date. (5th March 2021) - Arroyo, Marta; Ruiz, Francisco; Campos, Juan Manuel; Bermejo, Javier; González-Regalado, María Luz; Vidal, Joaquín Rodríguez; Cáceres, Luis Miguel; Olías, Manuel; Abad, Manuel; Izquierdo, Tatiana; Gómez, Paula; Toscano, Antonio; et al.
Abstract: On August 3, 1492, Christopher Columbus departed from the port of Palos de la Frontera, located in a small cove in southwestern Spain, and returned to this same port on March 15, 1493. On the basis of sedimentology, geochemistry, paleontology and dating of a long core (18 m) collected in this cove, thirteen facies are distinguished in the Neogene-Holocene evolution of its sedimentary infilling, with a transition from Miocene marine environments to Late Holocene marshes, going through an intermediate period that includes fluvial gravels, alluvial sediments and shallow coastal deposits that characterize the maximum of the Fladrian transgression in this area ( 6.5 cal kyr BP). These data and others contributed by historical sources allow an approximate reconstruction of this cove at the end of the 15th century. Graphical abstract: Image 1 Highlights: On August 3, 1492, Christopher Columbus departed from a cove in SW Spain. Its sedimentary record includes the transit from a Miocene shelf to alluvial sediments. Two geochemical peaks are related to the Flandrian transgression and Roman mining. In 1492, the progressive filling hindered navigability in this cove.